Sebuah Penelitian Urgensi Pelaksanaan Skrining Riwayat Kesehatan Peserta JKN-KIS dengan Pendekatan Stakeholder Engagement: Urgensi Skrining Riwayat Kesehatan Peserta JKN-KIS dan Kerangka Kerja Ray dan Miller sebagai metode Stakeholder Engagement - Nanda Elok Juwita; Dwi Santoso (Jurnal Jaminan Kesehatan Nasional, 2022)
Implementing health history screening is one of the main concerns at Badan Penyelenggara Jaminan Sosial Kesehatan Republik Indonesia (BPJS Kesehatan RI). Its implementation can be optimal if there is a good stakeholder engagement process. The purpose of this study is to analyze the urgency of health history screening. After that, the researcher uses Ray and Miller’s Framework from other studies and then compares the suitability of using the framework in the stakeholder engagement process that has been carried out in achieving health history screening at Kantor Cabang Singkawang (KC Singkawang). The method used in this study is a literature review combined with a comparison of the situation in the field. The use of references from various kinds of foreign and domestic research. Regarding the results, various data related to the five urgencies were found which ca,n be a strong reason that health history screening is mandatory for all Jaminan Kesehatan Nasional-Kartu Indonesia Sehat (JKN-KIS’s) participants and the Ray and Miller’s Framework is very suitable if applied further in the stakeholder engagement process at KC Singkawang. It is hoped that further research will be able to conduct quantitative research on the effect of  Ray and Miller’s Framework in implementing stakeholder engagement to achieve comprehensive health history screening